Mengeksplorasi Regulasi Industri Seksual di Indonesia: Pemidanaan Pembeli Jasa Pekerja Seks Komersial - Sonjaya, Saji (CIC Lembaga Riset dan Konsultan Sosial, 2025)
The sex industry in Indonesia is a phenomenon that has existed since the colonial era and has continued to develop both openly and covertly. The absence of explicit legal regulations on prostitution in Indonesia, combined with advancements in digital technology, has created new challenges in enforcing consistent regulations and has led to increased sexual exploitation, particularly of children. This study aims to explore the ambiguous regulations surrounding the commercial sex industry, focusing on voluntary sex work and sexual exploitation within the context of Indonesian law. This study employs a normative juridical research method, analyzing existing legal norms, including the Indonesian Penal Code, the Electronic Information and Transactions Law, and regional regulations governing prostitution. The findings indicate that Indonesia’s criminal policy targeting buyers of sexual services has not been entirely effective in reducing demand, as clients tend to shift to more discreet digital platforms. While this policy was expected to disrupt the industry, it has instead fostered the emergence of a black market that is more difficult to monitor, thereby increasing the risks of exploitation. Therefore, a more comprehensive policy approach is needed—one that not only focuses on criminalization but also ensures the protection of sex workers’ rights.